PENGGUNAAN MULTIMEDIA DAN ANIMASI INTERAKTIF TERHADAP KETERAMPILAN MEMBACA PERMULAAN SISWA - Andriyani Andriyani; Happy Indira Dewi; Zulfitria Zulfitria (Universitas Muhammadiyah Jakarta, 2020)
The purpose of this study was to determine the effect of the use of multimedia and interactive animation on early reading skills in early childhood. This research was conducted at TK Lab School FIP UMJ and Kindergarten Ketilang which involved 60 students in TK B group. The research method was using experimental research design statistics with 2x2 treatment with level design. The results of the multiple regression statistical analysis prove that multimedia and interactive animation have positive and significant effects. This can be proven from the results of the multiple regression statistical analysis it is known that Multimedia has a positive and significant effect on Early Reading Skills, meaning that multimedia and animation together (simultaneously) affect early reading skills.